2012
DOI: 10.5114/aoms.2012.28561
|View full text |Cite
|
Sign up to set email alerts
|

Low serum IgA and increased expression of CD23 on B lymphocytes in peripheral blood in children with regressive autism aged 3-6 years old

Abstract: IntroductionImmune system dysfunction is considered to be one of many medical disorders found in children with autism. The primary objective of the study was to assess if blood tests reflecting humoral immunity (IgA, IgG, IgM, IgE) are useful in identifying children with regressive autism. The secondary objective was to evaluate a part of the cellular arm of immunity (CD4/CD25 Tregs, CD4/CD23 cells) in those children.Material and methodsUsing a clinical case-control design, the systemic levels of immunoglobuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 43 publications
4
24
0
3
Order By: Relevance
“…Some of the studies have failed to show this correlation. 33,34 In the light of these findings we may speculate that the degree of immune activation differs among the autistic individuals which is consistent with the heterogeneous clinical manifestations of autism. Additionally in the lack of longitudinal studies, existing literature failed to reply the question of whether immune activation oscillates up or down in different immune pathways through the course of the ASD.…”
Section: Discussionmentioning
confidence: 57%
“…Some of the studies have failed to show this correlation. 33,34 In the light of these findings we may speculate that the degree of immune activation differs among the autistic individuals which is consistent with the heterogeneous clinical manifestations of autism. Additionally in the lack of longitudinal studies, existing literature failed to reply the question of whether immune activation oscillates up or down in different immune pathways through the course of the ASD.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, past reports showed that about 5% of ASD patients have IgA deficiency, and 30-40% have low serum IgA levels (Gupta et al 1996, Wasilewska et al 2012. ASD patients often display an enhanced sensitivity to gluten, with increased anti-gliadin antibodies compared to healthy individuals (Lau et al 2013).…”
Section: ↓↑mentioning
confidence: 99%
“…PBMCs obtained from ASD children produced more tumor necrosis factor-a (TNF-a)/interleukin-12 (IL-12) than those obtained from control subjects when challenged with casein, β -lactoglobulin, and α -lactalbumin [18]. Specific IgG to gluten was comparable among ASDs and controls [15]. A significant percentage of autistic sera were associated with elevated immunoglobulin IgG, IgM, or IgA antibodies against gliadin [21].…”
Section: Introductionmentioning
confidence: 99%